Application of Economic Order Quantity and Reorder Point Methods in Improving the Efficiency of Coffee Raw Material Supply (Case Study At PT. Herbal Salam) - Susi Susilowati; Ririn Restu Aria (IJISTECH (International Journal of Information System and Technology), 2022)
The food industry sector is currently getting tighter competition, especially in the form of food in the form of herbal drinks in the form of powders and liquids. That way it is necessary to control the supply of the right raw materials for the smooth production process. The purpose of this study is to find out and analyze the control of coffee raw material supplies applied by PT. Herbal Salam. So that it can improve the efficiency of raw material supply and can improve the performance of raw material management at PT. Herbal Salam.  The research methods used are the EOQ and ROP methods. Research results show that the company's raw material inventory has not been optimal and has not shown a minimum inventory cost. Based on analysis and policy calculations the company produces a total inventory of 72.000 per Kg in a year with an average purchase of 30 times a year, while the Economic Order Quantity (EOQ) method produces a total inventory of 5.280 per kg in a year with an average purchase of at least 14 times a year. This indicates that the EOQ method is smaller or there are savings of more than 50% compared to the company's policies.